Surface treatment method and surface-treated article
Patent Information
- Application Number
- JP2023095799
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-09
- Publication Date
- 2024-12-19
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
【0022】 本発明に係る表面処理方法は、環境負荷を低減できるとともに、強固な表面処理を行うことが可能である。
Smart Images

Figure 2024176922000001 
Figure 2024176922000002 
Figure 2024176922000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a surface treatment method such as a release treatment or a water repellency treatment, and to a surface-treated article produced by said method. [Background technology]
[0002] In general, a release sheet is formed by forming a release layer on at least one side of a substrate such as paper, a plastic film, polyethylene laminated paper, etc. Release sheets are widely used, for example, as protective sheets for pressure-sensitive adhesive layers in pressure-sensitive adhesive sheets, process films for producing resin sheets, process films for forming ceramic green sheets, process films for producing synthetic leather, etc.
[0003] The release layer of the release sheet is usually formed by applying a release agent composition containing a reactive compound onto a substrate and curing it. As the release agent composition for forming the release layer, for example, a silicone-based release agent composition containing a silicone compound such as a silicone resin, polysiloxane, or silicone oil is widely used.
[0004] Meanwhile, in recent years, a method of forming a specific release layer on a substrate using a dry process has also been considered. For example, Prior Art Document 1 discloses a film used in molding fiber-reinforced plastics, which is formed by forming a release layer on a plastic substrate by plasma chemical vapor deposition using a mixed gas composition containing an organosilicon compound having an Si-O bond in the molecule and a low-molecular carbon-containing compound.
[0005] In addition, a water-repellent layer is provided on at least a part of the surface of a substrate to impart water repellency. The above-mentioned silicone-based release agent composition may be used as the material for the water-repellent layer, and the method for forming the water-repellent layer may include applying the composition to the surface of the substrate and curing it, or may be formed by the above-mentioned dry process. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2012-045795 A Summary of the Invention [Problem to be solved by the invention]
[0007] As mentioned above, the release layer formed from the silicone-based release agent composition is generally formed by applying the silicone-based release agent composition on a substrate and curing it.Here, since it is difficult to apply the silicone-based release agent composition directly on a substrate to form a coating film, the silicone-based release agent composition is usually diluted with a large amount of organic solvent and then applied on the substrate.At this time, carbon dioxide is discharged by the disposal of the organic solvent used, and the burden on the environment is considered to be a problem.Therefore, if a release sheet can be manufactured without using organic solvent, it is effective in reducing the environmental burden.
[0008] Here, the manufacturing method using a dry process as in Patent Document 1 does not use organic solvents, and therefore can solve the above-mentioned environmental load problem. However, in the conventional manufacturing method using a dry process as in Patent Document 1, it is difficult to form a strong release layer and water-repellent layer, and there are problems in that the silicone component is likely to migrate from these layers to the surroundings, and that these layers are likely to collapse or dissolve when immersed in a certain solution.
[0009] The present invention has been made in consideration of the above-mentioned circumstances, and aims to provide a surface treatment method capable of reducing the environmental load and performing strong surface treatment, and a surface-treated article manufactured by the method. [Means for solving the problem]
[0010] In order to achieve the above object, firstly, the present invention provides a surface treatment method comprising: a preparation step of preparing a hydrosilyl group-containing compound having a hydrosilyl group in the molecule, an alkoxysilyl group-containing compound having an alkoxysilyl group in the molecule, a catalyst containing a Lewis acid, and a substrate; and a vapor deposition polymerization step of vapor-depositing the hydrosilyl group-containing compound, the alkoxysilyl group-containing compound, and the catalyst onto at least a part of the surface of the substrate, and polymerizing the hydrosilyl group-containing compound and the alkoxysilyl group-containing compound to form a silicon-containing polymer layer on the surface of the substrate (Invention 1).
[0011] In the surface treatment method according to the above invention (Invention 1), the above-mentioned hydrosilyl group-containing compound, alkoxysilyl group-containing compound and catalyst are prepared, and the surface treatment is carried out by vapor deposition polymerization of these on at least a part of the surface of the substrate, thereby making it possible to form a release layer or a water-repellent layer without using an organic solvent, thereby reducing the environmental load. Furthermore, the action of the catalyst causes the hydrosilyl group-containing compound and the alkoxysilyl group-containing compound to react, forming a structure in which they are well polymerized, making it possible to form a strong release layer or a water-repellent layer.
[0012] In the above invention (Invention 1), the hydrosilyl group-containing compound preferably contains at least two hydrosilyl groups in one molecule (Invention 2).
[0013] In the above invention (Invention 1 or 2), the alkoxysilyl group-containing compound preferably contains at least two alkoxysilyl groups in one molecule (Invention 3).
[0014] In the above inventions (Inventions 1 to 3), the hydrosilyl group-containing compound is represented by the following formula (1): SiR 1 (3-a) H a -(X)-SiR 2 (3-b) H b …(1) (In the above formula (1), a and b each independently represent an integer of 1 to 3; R 1 and R 2 are each independently an alkyl group having 1 to 8 carbon atoms, and (X) is a divalent aliphatic hydrocarbon group or a divalent organosiloxy group. It is preferable that the compound has a structure represented by the following formula (Invention 4):
[0015] In the above inventions (Inventions 1 to 4), the alkoxysilyl group-containing compound is represented by the following formula (2): SiR 3 (3-c) (OR 5 ) c -(Y)-SiR 4 (3-d) (OR 5 ) d …(2) (In the above formula (2), c and d each independently represent an integer of 1 to 3; R 3 and R 4 are each independently an alkyl group having 1 to 8 carbon atoms; R 5 is an alkyl group having 1 to 8 carbon atoms, and (Y) is a divalent aliphatic hydrocarbon group or a divalent organosiloxy group. It is preferable that the compound has a structure represented by the following formula (Invention 5): and has alkoxysilyl groups at both molecular terminals.
[0016] In the above inventions (Inventions 1 to 5), the Lewis acid preferably contains a boron atom (Invention 6).
[0017] In the above inventions (Inventions 1 to 6), the deposition in the deposition polymerization step is preferably ion-assisted deposition (Invention 7).
[0018] In the above inventions (Inventions 1 to 7), it is preferable that in the vapor deposition polymerization step, a compound that is gaseous under an environment of 1 atmospheric pressure and 23°C is eliminated by the reaction between the hydrosilyl group-containing compound and the alkoxysilyl group-containing compound (Invention 8).
[0019] First, the present invention provides a surface-treated article comprising a substrate and a silicon-containing polymer layer provided on at least a part of the surface of the substrate, the surface-treated article being produced by a surface treatment method including: a preparation step of preparing a hydrosilyl group-containing compound having a hydrosilyl group in its molecule, an alkoxysilyl group-containing compound having an alkoxysilyl group in its molecule, and a catalyst containing a Lewis acid; and a vapor deposition polymerization step of vapor-depositing the hydrosilyl group-containing compound, the alkoxysilyl group-containing compound, and the catalyst onto at least a part of the surface of the substrate, and polymerizing the hydrosilyl group-containing compound and the alkoxysilyl group-containing compound to form a silicon-containing polymer layer on the surface of the substrate (Invention 9).
[0020] In the above invention (Invention 9), it is preferred that the substrate is in the form of a sheet, the silicon-containing polymer layer is a release layer, and the surface-treated article is a release sheet (Invention 10).
[0021] In the above invention (Invention 9 or 10), the silicon-containing polymer layer is preferably a water-repellent layer (Invention 11). Effect of the Invention
[0022] The surface treatment method according to the present invention can reduce the environmental load and can perform robust surface treatment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] Hereinafter, an embodiment of the present invention will be described. The surface treatment method according to the present embodiment includes a preparation step of preparing a hydrosilyl group-containing compound having a hydrosilyl group in its molecule, an alkoxysilyl group-containing compound having an alkoxysilyl group in its molecule, a catalyst containing a Lewis acid, and a substrate; and a vapor deposition polymerization step of vapor-depositing the hydrosilyl group-containing compound, the alkoxysilyl group-containing compound, and the catalyst onto at least a portion of the surface of the substrate, and polymerizing the hydrosilyl group-containing compound and the alkoxysilyl group-containing compound to form a silicon-containing polymer layer on the surface of the substrate.
[0024] In the surface treatment method according to the present embodiment, as described above, the hydrosilyl group-containing compound, the alkoxysilyl group-containing compound and the catalyst are used as the three main materials, and the silicon-containing polymer layer is formed by vapor deposition polymerization of them on at least a part of the surface of the substrate.Therefore, the organic solvent for diluting the composition, which is required when applying the composition to the substrate to form a coating film, is not required in the surface treatment method according to the present embodiment, and the environmental load can be significantly reduced.
[0025] Furthermore, in the surface treatment method according to the present embodiment, the polymerization reaction between the hydrosilyl group in the hydrosilyl group-containing compound and the alkoxysilyl group in the alkoxysilyl group-containing compound proceeds in the formed vapor deposition film by the action of the catalyst. This allows the polymer of the hydrosilyl group-containing compound and the alkoxysilyl group-containing compound to be produced well, forming a strong silicon-containing polymer layer. Therefore, in the surface-treated article produced by the surface treatment method according to the present embodiment, the components contained in the silicon-containing polymer layer can be prevented from migrating to a member in contact with the layer, and the collapse and dissolution of the silicon-containing polymer layer can be prevented when the surface-treated article is immersed in various organic solvents.
[0026] In the surface treatment method according to the present embodiment, it is not necessary for the polymerization reaction between the alkoxysilyl group-containing compound and the alkoxysilyl group-containing compound to proceed completely in the silicon-containing polymer layer to be formed, and unreacted alkoxysilyl group-containing compound and alkoxysilyl group-containing compound may remain in the silicon-containing polymer layer.
[0027] 1. Preparation process In the above preparation step, the details of the above-mentioned three components and the base material are not particularly limited as long as they are prepared. In particular, the above-mentioned three components may be synthesized or commercially available.
[0028] (1) Hydrosilyl group-containing compounds The hydrosilyl group-containing compound in the present embodiment is not limited in detail as long as it has a hydrosilyl group in the molecule, but it is preferable that the hydrosilyl group-containing compound contains at least two hydrosilyl groups in one molecule.
[0029] A preferred specific example of the hydrosilyl group-containing compound in this embodiment is a compound represented by the following formula (1): SiR 1 (3-a) H a -(X)-SiR 2 (3-b) H b …(1) Examples of suitable compounds include compounds having hydrosilyl groups at both molecular terminals and having the structure represented by the following formula:
[0030] In the above formula (1), a and b each independently represent an integer of 1 to 3. It is particularly preferable that a and b are both 3.
[0031] In addition, in the above formula (1), R 1 and R 2are each independently an alkyl group having a carbon number of 1 to 8. Preferred examples of the alkyl group include a methyl group, an ethyl group, a propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, and a phenyl group, and among these, a methyl group is preferred.
[0032] Furthermore, in the above formula (1), (X) is a divalent aliphatic hydrocarbon group or a divalent organosiloxy group. Examples of the organosiloxy group include those having a repeating unit number of 2 to 50 diorganosiloxane units, and particularly preferably those having a repeating unit number of 20. The aliphatic hydrocarbon group and the organosiloxy group may each be linear or branched. When the aliphatic hydrocarbon group and the organosiloxy group are substituted, examples of the substituent include an alkyl group having 1 to 20 carbon atoms, a hydroxyl group, etc., and among these, an alkyl group having 1 to 6 carbon atoms is preferred, and a methyl group is particularly preferred.
[0033] Specific preferred examples of the hydrosilyl group-containing compound in this embodiment include hydrogen-terminated siloxanes and side-chain type hydrogen-modified silicones.
[0034] The weight average molecular weight of the hydrosilyl group-containing compound in the present embodiment is preferably 200 to 5000, particularly preferably 300 to 4000, and further preferably 400 to 3000. In addition, the method for measuring the weight average molecular weight in this specification refers to a value measured by the GPC method in terms of standard polystyrene.
[0035] (2) Alkoxysilyl group-containing compounds The details of the alkoxysilyl group-containing compound in the present embodiment are not limited as long as it has an alkoxysilyl group in the molecule, but it is preferable that the alkoxysilyl group-containing compound contains at least two alkoxysilyl groups in one molecule.
[0036] A preferred specific example is the compound represented by the following formula (2): SiR 3 (3-c) (OR 5 ) c -(Y)-SiR 4 (3-d) (OR 5 ) d …(2) Examples of suitable compounds include compounds having an alkoxysilyl group at both molecular terminals and having the structure represented by the following formula:
[0037] In the above formula (2), c and d each independently represent an integer of 1 to 3. It is particularly preferable that c and d are both 3.
[0038] In addition, in the above formula (2), R 3 and R 4 are each independently an alkyl group having 1 to 8 carbon atoms. Preferred examples of the alkyl group include a methyl group, an ethyl group, a propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, and a phenyl group, and among these, a methyl group is preferred. 5 is an alkyl group having a carbon number of 1 to 8. Preferred examples of the alkyl group include a methyl group, an ethyl group, a propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, and a phenyl group, and among these, a methyl group is preferred.
[0039] Furthermore, in the above formula (2), (Y) is a divalent aliphatic hydrocarbon group or a divalent organosiloxy group. Examples of the organosiloxy group include those having a repeating unit number of 2 to 50 diorganosiloxane units, and particularly preferably those having a repeating unit number of 20. The aliphatic hydrocarbon group and the organosiloxy group may each be linear or branched. When the aliphatic hydrocarbon group and the organosiloxy group are substituted, examples of the substituent include an alkyl group having 1 to 20 carbon atoms, a hydroxyl group, etc., and among these, an alkyl group having 1 to 6 carbon atoms is preferred, and a methyl group is particularly preferred.
[0040] Preferable specific examples of the alkoxysilyl group-containing compound in this embodiment include 1,6-bis(triethoxysilyl)hexane and silicone oligomers modified with alkoxy at both ends.
[0041] The weight average molecular weight of the alkoxysilyl group-containing compound in this embodiment is preferably 200 to 5,000, particularly preferably 300 to 4,000, and further preferably 400 to 3,000.
[0042] The amount of the alkoxysilyl group-containing compound used in this embodiment is preferably 5 to 100 parts by mass, more preferably 10 to 50 parts by mass, and even more preferably 15 to 30 parts by mass, per 100 parts by mass of the hydrosilyl group-containing compound used in this embodiment.
[0043] In addition, the amount of the alkoxysilyl group-containing compound used in this embodiment is preferably such that the ratio of the hydrosilyl group of the hydrosilyl group-containing compound to the alkoxysilyl group of the alkoxysilyl group-containing compound is 25:1 to 1:25, particularly preferably 5:1 to 1:5, and more preferably 2:1 to 1:2. This makes it easy to prevent these compounds from remaining unreacted in the silicon-containing polymer layer formed.
[0044] (3) Catalyst The catalyst in the present embodiment is not particularly limited as long as it contains a Lewis acid. Preferred examples of the Lewis acid include Lewis acids containing an atom selected from boron, aluminum, gallium, indium, titanium, etc. Among them, Lewis acids containing a boron atom are preferred from the viewpoint of easily and efficiently proceeding with the above-mentioned polymerization reaction.
[0045] Specific examples of the catalyst in this embodiment include tris(pentafluorophenyl)borane, tris(pentachlorophenyl)borane, triphenylborane, tris(pentafluorophenyl)borane, and the like. Among these, tris(pentafluorophenyl)borane is preferred from the viewpoint of easily and efficiently progressing the above-mentioned polymerization reaction.
[0046] The amount of the catalyst used in this embodiment is preferably 1 to 100 parts by mass, more preferably 10 to 80 parts by mass, and even more preferably 20 to 60 parts by mass, per 100 parts by mass of the hydrosilyl group-containing compound used in this embodiment.
[0047] (4) Other ingredients In the surface treatment method according to the present embodiment, other components may be used in addition to the above-mentioned hydrosilyl group-containing compound, alkoxysilyl group-containing compound, and catalyst. In this case, the other components may be vapor-deposited onto the substrate together with the three main components, or may be used by a method other than vapor deposition.
[0048] (5) Base material The material, shape, etc. of the substrate can be appropriately selected depending on the purpose. For example, examples of the material include resin, paper, metal, glass, etc. The shape may be a sheet or a three-dimensional shape. Details are as described below.
[0049] 2. Vapor deposition polymerization process In the vapor deposition polymerization step in the surface treatment method according to the present embodiment, the hydrosilyl group-containing compound, the alkoxysilyl group-containing compound, and the catalyst are vapor-deposited onto at least a portion of the surface of the substrate, and the hydrosilyl group-containing compound and the alkoxysilyl group-containing compound are polymerized to form a silicon-containing polymer layer on the surface of the substrate.
[0050] Here, the polymerization reaction between the hydrosilyl group-containing compound and the alkoxysilyl group-containing compound is based on the reaction between the hydrosilyl group in the hydrosilyl group-containing compound and the alkoxysilyl group in the alkoxysilyl group-containing compound due to the action of the catalyst, as described above.
[0051] Regarding this reaction, the reaction formula is exemplified below in the case where the hydrosilyl group-containing compound is a compound having a structure represented by the above formula (1) (particularly, a compound where a=1 and b=1) and the alkoxysilyl group-containing compound is a compound having a structure represented by the above formula (2) (particularly, a compound where c=1 and d=1). [ka]
[0052] As shown in the above reaction formula, the hydrosilyl group (SiH group) of the hydrosilyl group-containing compound and the alkoxysilyl group (SiOR 5 Between R 5 In particular, this reaction occurs when the vacant orbital of the Lewis acid in the catalyst captures a hydrogen atom in the hydrosilyl group to form an intermediate, which then transfers to the alkoxysilyl group that is approaching it, resulting in the formation of R 5 This is a reaction in which H is released and the silicon atom that formed the hydrosilyl group bonds with the oxygen atom that formed the alkoxysilyl group. This reaction proceeds at both ends of the hydrosilyl group-containing compound and the alkoxysilyl group-containing compound, respectively, to form a polymer in which these compounds are linked together.
[0053] The polymerization reaction between the hydrosilyl group-containing compound and the alkoxysilyl group-containing compound may proceed simultaneously with the formation of a vapor-deposited film on the surface of the substrate, or may proceed after completion of the formation of the vapor-deposited film, or may proceed both simultaneously with the formation of the vapor-deposited film and after that.
[0054] In addition, in the vapor deposition polymerization step of this embodiment, it is preferable that the reaction between the hydrosilyl group-containing compound and the alkoxysilyl group-containing compound causes a compound that is gaseous under an environment of 1 atmosphere and 23°C to be eliminated. In particular, since a condensation reaction occurs between the hydrosilyl group in the hydrosilyl group-containing compound and the alkoxysilyl group in the alkoxysilyl group-containing compound, it is preferable that the compound that is eliminated at this time is gaseous as described above. By eliminating the gaseous compound, the compound is less likely to remain in the silicon-containing polymer layer that is formed, and therefore it is easier to form a stronger silicon-containing polymer layer. Examples of compounds that are gaseous under an environment of 1 atmosphere and 23°C include alkanes, and in particular methane, ethane, propane, isopropane, and the like.
[0055] The deposition method (method of evaporating a material and attaching it to a substrate) in the deposition polymerization step in this embodiment may be any method including a step of supplying the hydrosilyl group-containing compound, the alkoxysilyl group-containing compound, and the catalyst gas, and may be any method such as physical vapor deposition (PVD) or chemical vapor deposition (CVD). For example, deposition methods such as vacuum deposition, ionization deposition, ion plating, ion-assisted deposition, plasma polymerization, and plasma CVD may be used. Among these, from the viewpoint of being able to effectively deposit using a relatively simple device, it is preferable to use the vacuum deposition method. In addition, from the viewpoint of being easy to form a stronger silicon-containing polymer layer, it is preferable to use the ion-assisted deposition method.
[0056] (1) Vacuum deposition method When performing a vacuum deposition method, it can be performed according to a known method. For example, gases of the three components, namely, the hydrosilyl group-containing compound, the alkoxysilyl group-containing compound, and the catalyst, are each supplied into a reduced pressure container and deposited on at least a portion of the surface of the substrate.
[0057] The above three gas components may be supplied, for example, by providing a container such as a crucible (hereinafter simply referred to as a "raw material container") outside a container such as a chamber that can be depressurized (hereinafter simply referred to as a "reduced pressure container"), evaporating or vaporizing the three components (liquid or solid at room temperature) in the crucible, and supplying them into the reduced pressure container using a raw material supply pipe or the like. Alternatively, the three components (liquid or solid at room temperature) may be evaporated or vaporized in a raw material container provided inside the reduced pressure container, and introduced into the reduced pressure container directly or via a raw material supply pipe or the like. In either case, one crucible may be used for each component, or multiple components may be placed in one crucible and evaporated or vaporized.
[0058] The reduced pressure vessel may be a known vacuum vessel that has been used in the past. The direction of release of the vaporized components can be controlled by directing the opening of the raw material vessel or the outlet of the raw material supply pipe connected to the raw material vessel toward the surface of the substrate that is the target of deposition. In other words, the method can be used to control the deposition portion on the substrate surface. The raw material supply pipe may be equipped with a valve mechanism or the like for controlling the discharge amount of the vaporized components.
[0059] The evaporation or vaporization of the above three components can be carried out, for example, by heating. The heating method is not particularly limited, and any known heating method can be used. The heating temperature can be appropriately set depending on the components used, but it is preferable that the temperature is such that these components do not thermally decompose.
[0060] The heating temperature of the hydrosilyl group-containing compound is, for example, preferably 170° C. or higher, more preferably 200° C. or higher, and even more preferably 230° C. or higher, from the viewpoint of accelerating the evaporation rate and shortening the time required to achieve a predetermined film thickness, while it is preferably 400° C. or lower, more preferably 350° C. or lower, and even more preferably 300° C. or lower, from the viewpoint of suppressing thermal deterioration of the material.
[0061] The heating temperature of the alkoxysilyl group-containing compound is, for example, preferably 130° C. or higher, more preferably 220° C. or higher, and even more preferably 250° C. or higher, from the viewpoint of accelerating the evaporation rate and shortening the time required to achieve a predetermined film thickness. On the other hand, from the viewpoint of suppressing thermal deterioration of the material, the heating temperature is preferably 400° C. or lower, more preferably 350° C. or lower, and even more preferably 300° C. or lower.
[0062] The heating temperature of the catalyst is, for example, preferably 40° C. or higher, more preferably 45° C. or higher, and even more preferably 50° C. or higher, from the viewpoint of accelerating the evaporation rate and shortening the time required to achieve a predetermined film thickness. On the other hand, from the viewpoint of suppressing thermal deterioration of the material, the heating temperature is preferably 100° C. or lower, more preferably 80° C. or lower, and even more preferably 60° C. or lower.
[0063] The pressure (vacuum degree) in the reduced pressure vessel is not particularly limited as long as the desired silicon-containing polymer layer can be formed, but is preferably 2.0×10 -5 Torr or less, preferably 1.5×10 -5 Torr or less, more preferably 1.0×10 -5 Torr or less. By setting the vacuum degree in this way, the probability that the adsorbed gas components other than the raw materials forming the silicon-containing polymer layer present in the reduced pressure container are mixed into the silicon-containing polymer layer is reduced, and a better quality silicon-containing polymer layer is easily obtained.
[0064] (2) Ion-assisted deposition When carrying out ion-assisted deposition, it is preferable to carry out ion irradiation on the region of the substrate to be deposited at the same time as or after the above-mentioned deposition.This makes the polymerization reaction between the hydrosilyl group-containing compound and the alkoxysilyl group-containing compound more likely to proceed, and makes it easier to form a strong silicon-containing polymer layer.It should be noted that, in the deposition polymerization process of this embodiment, ion irradiation is not essential to proceed with the above-mentioned polymerization reaction.Therefore, in the deposition polymerization process of this embodiment, ion irradiation is not essential, and for example, only the above-mentioned vacuum deposition method may be carried out.
[0065] The above-mentioned ions are not particularly limited, but from the viewpoint of safety, those which are easy to handle and easily exhibit adhesion to the substrate are preferred, for example, ionized argon, helium, neon, nitrogen, oxygen, or carbon dioxide. Among them, from the viewpoint of easily forming a strong and low-polarity silicon-containing polymer layer, it is preferred to use one or more ions selected from the group consisting of argon, helium, and neon.
[0066] The ions can be obtained by ionizing the gas of each molecule using a known ion generating device. Examples of the ion generating device include an electron generating device that has a cathode made of a tungsten filament on the outside and a grid-shaped anode on the inside, and can be filled with a gas that is the raw material for ions. In such an electron generating device, the tungsten filament of the cathode is heated by current to generate thermoelectrons, and a voltage is applied so that the thermoelectrons move toward the grid-shaped anode, and the thermoelectrons collide with the gas, thereby ionizing the gas.
[0067] In addition, for example, a raw material that can be turned into plasma among the gases is ionized by a plasma generator or the like to generate plasma, and the target ions (for example, argon ions (Ar + )) may be extracted and the ion may be used.
[0068] The ions generated as described above may be irradiated onto the surface of the substrate by applying an ion acceleration voltage as described below. In addition, ions irradiated from a known device such as an ion gun or plasma gun may also be used.
[0069] In the above-mentioned ion irradiation, it is preferable that the ion irradiation section of the ion generating device irradiates ions toward the surface side of the substrate on which deposition is to be performed, that is, the deposition surface of the substrate.
[0070] Ion irradiation conditions can be appropriately selected according to the properties of the hydrosilyl group-containing compound, the alkoxysilyl group-containing compound and the catalyst, but as one embodiment, the ion irradiation is preferably performed by applying a voltage (ion acceleration voltage) to the ions to accelerate the ions. The ion acceleration voltage is not particularly limited, but from the viewpoint of easily forming a strong silicon-containing polymer layer, it is preferably 0.1 kV or more, more preferably 0.2 kV or more, particularly preferably 0.3 kV or more, and even more preferably 0.5 kV or more. Also, from the same viewpoint, it is preferably 10.0 kV or less, more preferably 5.0 kV or less, particularly preferably 3.0 kV or less, and even more preferably 2.0 kV or less.
[0071] The ion irradiation may be changed in the middle of the process. For example, ion irradiation may be performed in the initial stage, but the ion irradiation may be stopped at a predetermined timing. In this way, by performing ion irradiation in the initial stage, adhesion between the substrate and the deposition film can be exhibited, and at the same time, by stopping the ion irradiation in the middle, it becomes easy to obtain a deposition film with low polarity and light peelability without modifying the deposit in the latter half of the deposition. The timing to stop the ion irradiation can be determined, for example, based on the thickness of the deposition film to be formed. As an example, ion irradiation can be provided at a stage where half of the target thickness is reached.
[0072] The method of applying the ion acceleration voltage is not particularly limited, but from the viewpoint of irradiating the accelerated ions more easily, it is preferable to apply a voltage to a substrate holder for holding the substrate. The substrate holder for holding the substrate is preferably a substrate holder provided in a reduced pressure vessel and capable of applying a voltage, and a substrate holder capable of adjusting the temperature can also be used. The substrate holder may be fixed, or may move at a constant speed such as a rotating drum or conveyor so as to enable continuous production. During continuous production, a long surface-treated article may be produced by operating the apparatus while holding, for example, a long resin sheet as the substrate on the substrate holder.
[0073] From the viewpoint of the film strength of the silicon-containing polymer layer, ion irradiation was performed on a deposition area of 1 cm 2 The ion irradiation dose is 0.01 μA / cm 2 From the same viewpoint, the ion irradiation dose is more preferably 0.05 μA / cm 2 More preferably, 0.2 μA / cm 2 More preferably, 0.4 μA / cm 2 From the viewpoint of suppressing side reactions, the ion irradiation dose is preferably 1000 μA / cm 2 Less than or equal to 500 μA / cm 2 Below 200 μA / cm, particularly preferably 2 Less than 100 μA / cm, more preferably 2 Since the ion irradiation amount varies, the maximum value of the variation range of the ion irradiation amount is defined as the "ion irradiation amount".
[0074] When the gas serving as the ion source is introduced into a depressurized vessel for ion irradiation, the pressure (degree of vacuum) in the depressurized vessel is not particularly limited as long as the silicon-containing polymer layer can be formed. For example, from the viewpoint of reducing the load on the equipment for depressurizing the depressurized vessel, it is preferably 5.0×10 -5 Torr or less, preferably 4.0×10 -5 Torr or less, preferably 3.0×10-5 The lower limit of the pressure is not particularly limited, but from the viewpoint of facilitating the formation of the silicon-containing polymer layer, the pressure is preferably equal to or higher than the above-mentioned preferred pressure for deposition, and more preferably 2.0×10 Torr or less. -5 Torr or higher.
[0075] Instead of the above ion-assisted deposition method, a method of irradiating energy rays together with vacuum deposition may be adopted to promote the polymerization reaction. Examples of the energy rays include known gamma rays, electron beams, ultraviolet rays, etc., and from the viewpoint of easily obtaining good adhesion, it is preferable to use either gamma rays or electron beams.
[0076] In the above-mentioned energy ray irradiation, it is preferable that the energy ray irradiation section of the energy ray generating device irradiates energy toward the surface side of the substrate on which deposition is to be performed, that is, the deposition surface of the substrate.
[0077] The conditions of energy beam irradiation, such as the illuminance and light amount of the energy beam, can be appropriately selected depending on the characteristics of the hydrosilyl group-containing compound, the alkoxysilyl group-containing compound, and the catalyst.
[0078] From the viewpoint of obtaining sufficient adhesion between the silicon-containing polymer layer and the substrate, it is more preferable to perform the deposition and the ion irradiation or the energy ray irradiation simultaneously. By performing the deposition and the energy ray irradiation simultaneously, each component is deposited on the surface of the substrate and collides with ions, etc., to form bonds with the substrate surface and bonds between the material molecules, so that it is considered that unreacted components are less likely to remain in the obtained silicon-containing polymer layer. In addition, the energy of ions, etc. is most kinetically transmitted to the surface of the deposition film where ions, etc. collide, so that each component is activated and the reaction proceeds more easily. On the other hand, the deeper the deposition film (the part closer to the substrate side), the less energy is provided for the reaction of each component because it becomes the collision energy of the molecules that collide secondary and tertiary. Therefore, by performing the deposition and the ion irradiation or the energy ray irradiation simultaneously, the collision energy of ions, etc. can be more effectively utilized, the reaction of each component is more likely to proceed, and it is considered that unreacted components are less likely to remain in the obtained silicon-containing polymer layer. Therefore, it is considered that by performing the deposition and the ion irradiation or the energy ray irradiation simultaneously, it is easier to achieve sufficient adhesion of the silicon-containing polymer layer to the substrate.
[0079] As described above, the vacuum vessel used is not particularly limited, and a vacuum vessel used in known deposition polymerization can be used. In addition to the various devices described above, the vacuum vessel may be equipped with other equipment such as a shutter for blocking deposition of each component or irradiation of ions or the like onto the substrate surface, a film thickness monitor for measuring the thickness of the deposition film or silicon-containing polymer layer, a pressure monitor, a neutralizer, a trap for desired components, and an exhaust system, if necessary.
[0080] 3. Surface treatment items The surface-treated article produced by the surface treatment method according to the present embodiment includes a substrate and a silicon-containing polymer layer provided on at least a portion of the substrate. The surface-treated article according to the present embodiment can be used as a release sheet, a water-repellent article, etc., depending on the composition, physical properties, shape, etc. of the substrate and the silicon-containing polymer layer.
[0081] (1) Release sheet When the surface-treated article of the present embodiment is produced as a release sheet, the substrate is preferably in the form of a sheet, and in this case, the silicon-containing polymer layer functions as a release layer.
[0082] The thickness of the substrate can be appropriately set according to the use of the release sheet. In general, from the viewpoint of handling, the thickness is preferably 10 μm or more, particularly preferably 15 μm or more, and more preferably 20 μm or more. From the same viewpoint, the thickness of the substrate is preferably 500 μm or less, particularly preferably 300 μm or less, and more preferably 200 μm or less.
[0083] The material of the substrate is not particularly limited as long as it can laminate a silicon-containing polymer layer (release layer). Examples of such substrates include polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate, polyvinyl chloride, polystyrene, polyurethane, polycarbonate, polyamide, polyimide, polyetherimide, poly(meth)acrylic acid ester, polybutene, polybutadiene, polymethylpentene, acrylic urethane, cycloolefin polymer, polyphenylene sulfide, ethylene-vinyl acetate copolymer, ethylene-(meth)acrylic acid copolymer, ethylene-(meth)acrylic acid ester copolymer, ABS resin, ionomer resin, and various thermoplastic elastomers, and resin films made of these resins, and laminated films thereof; sheet materials made of papers such as fine paper, coated paper, glassine paper, craft paper, and polyethylene laminated paper. These sheet materials may be single-layered or multi-layered, consisting of two or more layers of the same or different types.
[0084] The resin film may contain known fillers, colorants, antistatic agents, antioxidants, organic lubricants, catalysts, etc. Furthermore, the resin film may be transparent, or may be colored, etc., as desired.
[0085] In the resin film, in order to improve the adhesion with the silicon-containing polymer layer (peeling layer) provided on the surface, one or both sides can be subjected to a surface treatment such as an oxidation method or a roughening method, or a primer treatment, if desired. Examples of the oxidation method include corona discharge treatment, plasma discharge treatment, chromium oxidation treatment (wet), flame treatment, hot air treatment, ozone, and ultraviolet irradiation treatment, and examples of the roughening method include sandblasting and thermal spraying treatment. These surface treatment methods are appropriately selected according to the type of plastic film, but generally, corona discharge treatment is preferably used in terms of effectiveness and operability.
[0086] The release force of the release sheet produced by the surface treatment method according to this embodiment can be appropriately set according to the application. For example, the release force is preferably 2000 mN / 20 mm or less, more preferably 1000 mN / 20 mm or less, and most preferably 500 mN / 20 mm or less. According to the surface treatment method according to this embodiment, a release sheet having a low release force as described above can be produced. On the other hand, in consideration of handling properties, the release force is preferably 10 mN / 20 mm or more, particularly preferably 20 mN / 20 mm or more, and more preferably 30 mN / 20 mm or more. Details of the method for measuring the release force in this specification are as described in the test examples described later.
[0087] (2) Water-repellent treated items When the surface-treated article in this embodiment is manufactured as a water-repellent treated article, the material, shape, etc. of the substrate can be appropriately selected according to the purpose. For example, examples of the substrate material include glass, metal, resin, etc. When a glass substrate is used, a water-repellent treated window material can be obtained as the water-repellent treated article. When a metal substrate is used, a water-repellent treated building steel material can be obtained as the water-repellent treated article. When a resin substrate is used, a water-repellent treated decorative sheet, marking film, etc. can be obtained as the water-repellent treated article. The substrate may be in the form of a sheet or a three-dimensional shape.
[0088] When the surface-treated article of this embodiment is manufactured as a water-repellent treated article, the silicon-containing polymer layer functions as a water-repellent layer. Regarding water repellency, the static contact angle on the surface of the water-repellent layer opposite to the substrate can be appropriately selected according to the purpose of water repellency, but is preferably, for example, 90° or more, particularly preferably 93° or more, and more preferably 95° or more. The upper limit of the static contact angle can also be appropriately selected, and is preferably, for example, 110° or less, particularly preferably 105° or less, and more preferably 100° or less.
[0089] The above-described embodiments are described for the purpose of facilitating understanding of the present invention, and are not described for the purpose of limiting the present invention. Therefore, each element disclosed in the above embodiment is intended to include all design modifications and equivalents that fall within the technical scope of the present invention. EXAMPLES
[0090] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to these examples.
[0091] [Peeling treatment] Example 1 A polyethylene terephthalate film having a thickness of 100 μm (manufactured by Mitsubishi Chemical Corporation, product name "Diafoil (registered trademark) T100") was prepared as a substrate, and the substrate was held on a substrate holder in a chamber, which is a reduced pressure vessel. Meanwhile, three crucibles were placed in the chamber as raw material vessels. Then, each of these crucibles was filled with a double-ended hydrogen siloxane (manufactured by Mitsubishi Chemical Corporation, product name "DMS-H11", described as "A-1" in Table 1) as a hydrosilyl group-containing compound, 1,6-bis(triethoxysilyl)hexane (manufactured by Tokyo Chemical Industry Co., Ltd., molecular weight: 326.54 g / mol, described as "B-1" in Table 1) as an alkoxysilyl group-containing compound, and tris(pentafluorophenyl)borane (manufactured by Tokyo Chemical Industry Co., Ltd., molecular weight: 511.88 g / mol) as a catalyst, in the masses described in Table 1. Thereafter, the degree of vacuum in the chamber was reduced to 1.0×10 -5 The pressure was reduced to Torr.
[0092] Next, the crucible filled with the hydrosilyl group-containing compound was heated to 170°C, the crucible filled with the alkoxysilyl group-containing compound was heated to 130°C, and the crucible filled with the catalyst was heated to 60°C, respectively, to evaporate the three materials. The evaporated three materials were discharged from the crucible toward one surface of the substrate, and the three materials were vapor-deposited on the substrate surface by this operation. As a result, a release sheet was obtained on one side of the substrate, which was provided with a silicon-containing polymer layer (release layer) having a thickness of 100 nm, which was formed by polymerizing the hydrosilyl group-containing compound and the alkoxysilyl group-containing compound.
[0093] The thickness of the substrate was measured using a constant pressure thickness measuring device (manufactured by Teclock, product name "PG-02J") in accordance with JIS K6783:1994, JIS Z1702:1994 and JIS Z1709:1995. The thickness of the release layer was measured using a spectroscopic ellipsometer (manufactured by J.A. Woollam Japan, product name "M-2000"). The same applies to the following examples and comparative examples.
[0094] Example 2 A polyethylene terephthalate film having a thickness of 100 μm (manufactured by Mitsubishi Chemical Corporation, product name "Diafoil (registered trademark) T100") was prepared as a substrate, and the substrate was held on a substrate holder in a chamber, which is a reduced pressure vessel. Meanwhile, three crucibles were placed in the chamber as raw material vessels. Then, each of these crucibles was filled with a double-ended hydrogen siloxane (manufactured by Mitsubishi Chemical Corporation, product name "DMS-H11", described as "A-1" in Table 1) as a hydrosilyl group-containing compound, 1,6-bis(triethoxysilyl)hexane (manufactured by Tokyo Chemical Industry Co., Ltd., molecular weight: 326.54 g / mol, described as "B-1" in Table 1) as an alkoxysilyl group-containing compound, and tris(pentafluorophenyl)borane (manufactured by Tokyo Chemical Industry Co., Ltd., molecular weight: 511.88 g / mol) as a catalyst, in the masses described in Table 1. Thereafter, the degree of vacuum in the chamber was reduced to 1.0×10 -5 The pressure was reduced to Torr.
[0095] Meanwhile, a vacuum level of 2.0×10 was achieved in the chamber by using an electron generator that was filled with argon gas and had a tungsten filament cathode on the outside and a grid-shaped anode on the inside of the chamber. -5 Argon gas was introduced to a pressure of Torr.
[0096] Next, the crucible filled with the hydrosilyl group-containing compound was heated to 170°C, the crucible filled with the alkoxysilyl group-containing compound was heated to 130°C, and the crucible filled with the catalyst was heated to 60°C, respectively, to evaporate the three materials. At the same time as the heating, the tungsten filament was heated, and a voltage was applied so that the thermoelectrons generated from the heated tungsten filament were directed toward the grid-shaped anode. This operation ionized the argon gas.
[0097] Furthermore, a predetermined voltage (substrate voltage (ion acceleration voltage)) was applied to the substrate holder holding the substrate. In this way, ion irradiation was performed on the three materials to be deposited on the substrate surface. The ion irradiation dose of the ion irradiation was adjusted by controlling the amount of thermal electrons from the electron generator. 2 The ion irradiation dose per unit time was as shown in Table 1.
[0098] In this manner, a release sheet was obtained which had a release layer having a thickness of 100 nm and which was formed by polymerizing the hydrosilyl group-containing compound and the alkoxysilyl group-containing compound on one side of the substrate.
[0099] Example 3 A polyethylene terephthalate film having a thickness of 100 μm (manufactured by Mitsubishi Chemical Corporation, product name "Diafoil (registered trademark) T100") was subjected to ozone treatment for 20 minutes using a UV ozone cleaner (manufactured by Japan Laser Electronics Co., Ltd., product name "NLUV2535"). A release sheet was obtained in the same manner as in Example 1, except that the film was used as a substrate and the amounts of the hydrosilyl group-containing compound, the alkoxysilyl group-containing compound, and the catalyst used were changed as shown in Table 1.
[0100] [Examples 4 to 5] A release sheet was obtained in the same manner as in Example 2, except that a substrate that had been subjected to ozone treatment in the same manner as in Example 3 was used, the amounts of the hydrosilyl group-containing compound, the alkoxysilyl group-containing compound, and the catalyst used were changed as shown in Table 1, and the amount of ions in the ion irradiation was changed as shown in Table 1.
[0101] Example 6 A release sheet was obtained in the same manner as in Example 4, except that the amounts of the hydrosilyl group-containing compound, the alkoxysilyl group-containing compound, and the catalyst used were changed as shown in Table 1, and the ion irradiation was stopped when the release layer exceeded half of the target thickness, and thereafter, deposition was continued to the target thickness without ion irradiation.
[0102] Example 7 A release sheet was obtained in the same manner as in Example 6, except that the amounts of the hydrosilyl group-containing compound and catalyst used were changed as shown in Table 1, and the amount of ions in the ion irradiation was changed as shown in Table 1.
[0103] [Examples 8 to 10] A release sheet was obtained in the same manner as in Example 4, except that the types of hydrosilyl group-containing compound and alkoxysilyl group-containing compound were changed as shown in Table 1, and the amounts of hydrosilyl group-containing compound, alkoxysilyl group-containing compound, and catalyst used were changed as shown in Table 1.
[0104] The hydrosilyl group-containing compound shown in "A-2" in Table 1 used in Examples 8 and 10 is a side-chain hydrogen-modified silicone (manufactured by Shin-Etsu Chemical Co., Ltd., product name "KF-99"). The heating temperature of the crucible filled with this hydrosilyl group-containing compound was set to 200°C. The alkoxysilyl group-containing compound shown in "B-2" in Table 1 is a silicone oligomer modified with alkoxy at both ends (manufactured by Momentive Performance Materials Japan, LLC, product name "XC-96-C2813"). The heating temperature of the crucible filled with this alkoxysilyl group-containing compound was set to 220°C.
[0105] Comparative Example 1 A release sheet was obtained in the same manner as in Example 7, except that no alkoxysilyl group-containing compound was used and the amounts of the hydrosilyl group-containing compound and catalyst used were changed as shown in Table 1.
[0106] Comparative Example 2 A release sheet was obtained in the same manner as in Example 5, except that no alkoxysilyl group-containing compound was used and the amounts of the hydrosilyl group-containing compound and catalyst used were changed as shown in Table 1.
[0107] [Test Example 1] (Evaluation of Adhesion) The release layer side of the release sheets produced in the Examples and Comparative Examples was rubbed with a finger, and the presence or absence of the release layer falling off was visually confirmed. Then, the adhesion between the release layer and the substrate was evaluated based on the following criteria. The results are shown in Table 1. 1: The peeling layer fell off. 2: The peeled layer did not fall off, but the surface was scraped off (smeared). 3: The peeled layer did not fall off and the surface was not scraped off.
[0108] [Test Example 2] (Measurement of peeling force) The release sheets obtained in the examples and comparative examples were stored for at least one day under an environment of 23°C and 50% RH to be used as the release sheets to be tested. A 20 mm wide adhesive tape (manufactured by Nitto Denko Corporation, product name "No. 31B") was attached to the release surface of the release sheet by rolling a 2 kg roller back and forth once, and then left to stand for 30 minutes under an environment of 23°C and 50% RH to be used as a sample for measuring the peel strength. The sample was fixed to a universal tensile tester (manufactured by Shimadzu Corporation, product name "Autograph AGS-20NX"), and the peel strength (mN / 20 mm) of the release sheet was measured by peeling the adhesive tape from the release layer in the 180° direction at a tensile speed of 300 mm / min in accordance with JIS Z0237:2009. The measurement results are shown in Table 1.
[0109] [Test Example 3] (Measurement of silicone transfer amount) For the adhesive surface of the adhesive tape used in Test Example 2, the silicon atom ratio (atomic %) was calculated using the following formula based on the amounts of silicon atoms (Si), carbon atoms (C) and oxygen atoms (O) (XPS count numbers) measured by X-ray photoelectron spectroscopy (XPS). The results are shown in Table 1. Note that a higher silicon atom ratio indicates a greater amount of silicone component transferred. Silicon atom ratio (atomic %) = [(Si element amount) / {(C element amount)+(O element amount)+(Si element amount)}]×100
[0110] [Table 1]
[0111] As can be seen from Table 1, the release sheet produced by the surface treatment method according to the embodiment exhibited sufficient releasability while being able to sufficiently reduce the amount of silicone component migration. Furthermore, as is clear from the above description of the surface treatment method, the surface treatment method according to the embodiment can be carried out without using an organic solvent, and can reduce the environmental load.
[0112] [Water-repellent treatment] Example 11 Glass on which aluminum was vapor-deposited was prepared as a substrate, and the substrate was held on a substrate holder in a chamber, which was a reduced pressure vessel. At this time, the substrate was set so that the vapor-deposited surface of the aluminum was subjected to a water-repellent treatment, which will be described later. Meanwhile, three crucibles were set in the chamber as raw material vessels. Then, each of these crucibles was filled with a double-ended hydrogen siloxane (manufactured by Mitsubishi Chemical Corporation, product name "DMS-H11") as a hydrosilyl group-containing compound, 1,6-bis(triethoxysilyl)hexane (manufactured by Tokyo Chemical Industry Co., Ltd., molecular weight: 326.54 g / mol, shown as "B-1" in Table 2) as an alkoxysilyl group-containing compound, and tris(pentafluorophenyl)borane (manufactured by Tokyo Chemical Industry Co., Ltd., molecular weight: 511.88 g / mol) as a catalyst, in the masses shown in Table 2. Thereafter, the degree of vacuum in the chamber was reduced to 1.0×10 -5 The pressure was reduced to Torr.
[0113] Next, the crucible filled with the hydrosilyl group-containing compound was heated to 170°C, the crucible filled with the alkoxysilyl group-containing compound was heated to 130°C, and the crucible filled with the catalyst was heated to 60°C, respectively, to evaporate the three materials. The evaporated three materials were discharged from the crucible toward one surface of the substrate, and the three materials were vapor-deposited on the substrate surface by this operation. As a result, a water-repellent treated article was obtained having a water-repellent layer having a thickness of 100 nm formed by polymerization of the hydrosilyl group-containing compound and the alkoxysilyl group-containing compound on one side of the substrate.
[0114] [Examples 12 to 13] Water-repellent treated articles were obtained in the same manner as in Example 11, except that the type of alkoxysilyl group-containing compound was changed as shown in Table 2, and the amounts of hydrosilyl group-containing compound, alkoxysilyl group-containing compound, and catalyst used were changed as shown in Table 2.
[0115] The alkoxysilyl group-containing compound shown in "B-2" in Table 2 used in Examples 12 and 13 was a silicone oligomer modified with alkoxy at both ends (manufactured by Momentive Performance Materials Japan, LLC, product name "XC-96-C2813"). The heating temperature of the crucible filled with this alkoxysilyl group-containing compound was set to 220°C.
[0116] Comparative Example 3 Water-repellent treated articles were obtained in the same manner as in Example 11, except that no hydrosilyl group-containing compound was used and the amounts of the alkoxysilyl group-containing compound and catalyst used were changed as shown in Table 2.
[0117] Comparative Example 4 Water-repellent treated articles were obtained in the same manner as in Example 11, except that no catalyst was used and the amounts of the hydrosilyl group-containing compound and the alkoxysilyl group-containing compound used were changed as shown in Table 2.
[0118] Comparative Example 5 Water-repellent treated articles were obtained in the same manner as in Example 11, except that the alkoxysilyl group-containing compound and catalyst were not used and the amount of the hydrosilyl group-containing compound used was changed as shown in Table 2.
[0119] [Test Example 4] (Confirmation of the presence or absence of hydrosilyl groups) The water-repellent treated articles produced in the examples and comparative examples were analyzed by Fourier transform infrared spectroscopy (FT-IR) using a high sensitivity reflectance method (RAS method) to determine the wavenumber (2000-2150 cm) of vibration stretching derived from the hydrosilyl (Si-H) group contained in the hydrosilyl group-containing compound. -1) was observed to see whether it had disappeared or remained. The results are shown in Table 2. Note that, in Comparative Example 3, which did not use a hydrosilyl group-containing compound, water repellency was obtained, but the Si-H group had not accumulated to such an extent that the spectrum could be detected, and the presence or absence of the Si-H group could not be confirmed.
[0120] In the above test, examples evaluated as "disappeared" mean that the hydrosilyl group of the hydrosilyl group-containing compound disappears due to the reaction with the alkoxysilyl group of the alkoxysilyl group-containing compound. In other words, it means that the reaction between the alkoxysilyl group-containing compound and the hydrosilyl group-containing compound proceeds well. In contrast, examples evaluated as "remaining" mean that the reaction between the alkoxysilyl group-containing compound and the hydrosilyl group-containing compound does not proceed sufficiently.
[0121] [Test Example 5] (Measurement of static contact angle) 2 μl of pure water was dropped onto the water-repellent treated surfaces of the water-repellent treated articles produced in the Examples and Comparative Examples under an environment of 23° C. and 50% RH, and the static contact angle (°) was measured using a fully automatic contact angle meter (manufactured by Kyowa Interface Science Co., Ltd., product name "DM701"). The results are shown in Table 2.
[0122] [Test Example 6] (Measurement of film thickness ratio after immersion) The water-repellent treated articles produced in the Examples and Comparative Examples were cut to a size of 2.0 cm x 2.5 cm to prepare measurement samples. The measurement samples were immersed in 20 ml of acetone at 23°C for 2 hours. Thereafter, the thickness of the release layer was measured using a microscope (manufactured by Keyence Corporation, product name "Nanoscale Hybrid Microscope VN-8000 / 8010"). The film thickness ratio (%) after immersion was calculated from the following formula. The results are shown in Table 1. Film thickness ratio (%) = (film thickness after immersion test) / (film thickness before immersion test)
[0123] [Table 2]
[0124] As can be seen from Table 2, the release sheet manufactured by the surface treatment method according to the embodiment exhibited sufficient water repellency. And, since the absorption spectrum derived from the hydrosilyl group disappeared, it was found that the reaction between the hydrosilyl group-containing compound and the alkoxysilyl group-containing compound in the water-repellent layer had progressed sufficiently. Furthermore, since the water-repellent layer remained sufficiently even after immersion in acetone, it was found that the water-repellent layer was firmly cured. Also, as is clear from the above description of the surface treatment method, the surface treatment method according to the embodiment can be carried out without using an organic solvent, and the environmental load can be reduced. [Industrial Applicability]
[0125] The surface treatment method of the present invention can be suitably used for the production of release sheets and water repellent treatment of articles. Furthermore, the surface treatment method of the present invention is expected to be applied in fields such as antifouling treatment of articles, antirust treatment, production of airbags (silicone-impregnated fabrics), and easy-slip treatment for sliding members, etc.
Claims
1. a preparation step of preparing a hydrosilyl group-containing compound having a hydrosilyl group in the molecule, an alkoxysilyl group-containing compound having an alkoxysilyl group in the molecule, a catalyst containing a Lewis acid, and a substrate; a vapor deposition polymerization step of depositing the hydrosilyl group-containing compound, the alkoxysilyl group-containing compound, and the catalyst on at least a part of the surface of the base material, and polymerizing the hydrosilyl group-containing compound and the alkoxysilyl group-containing compound to form a silicon-containing polymer layer on the surface of the base material; A surface treatment method comprising the steps of:
2. 2. The surface treatment method according to claim 1, wherein the hydrosilyl group-containing compound contains at least two hydrosilyl groups in one molecule.
3. 2. The surface treatment method according to claim 1, wherein the alkoxysilyl group-containing compound contains at least two alkoxysilyl groups in one molecule.
4. The hydrosilyl group-containing compound is represented by the following formula (1): SiR 1 (3-a) H a -(X)-SiR 2 (3-b) H b …(1) In the above formula (1), a and b each independently represent an integer of 1 to 3; 1 and R 2 are each independently an alkyl group having 1 to 8 carbon atoms, and (X) is a divalent aliphatic hydrocarbon group or a divalent organosiloxy group.
2. The surface treatment method according to claim 1, wherein the compound has a structure represented by the following formula:
5. The alkoxysilyl group-containing compound is represented by the following formula (2): SiR 3 (3-c) (OR 5 ) c -(Y)-SiR 4 (3-d) (OR 5 ) d …(2) In the above formula (2), c and d each independently represent an integer of 1 to 3; 3 and R 4 are each independently an alkyl group having 1 to 8 carbon atoms; R 5 is an alkyl group having 1 to 8 carbon atoms, and (Y) is a divalent aliphatic hydrocarbon group or a divalent organosiloxy group.
2. The surface treatment method according to claim 1, wherein the compound has a structure represented by the following formula:
6. 2. The surface treatment method according to claim 1, wherein the Lewis acid contains a boron atom.
7. 2. The surface treatment method according to claim 1, wherein the deposition in the deposition polymerization step is ion-assisted deposition.
8. 2. The surface treatment method according to claim 1, wherein in the vapor deposition polymerization step, a compound that is gaseous in an environment of 1 atmospheric pressure and 23° C. is released by the reaction between the hydrosilyl group-containing compound and the alkoxysilyl group-containing compound.
9. A surface-treated article comprising a substrate and a silicon-containing polymer layer provided on at least a portion of the substrate, The surface-treated article is a preparation step of preparing a catalyst containing a hydrosilyl group-containing compound having a hydrosilyl group in the molecule, an alkoxysilyl group-containing compound having an alkoxysilyl group in the molecule, and a Lewis acid; a vapor deposition polymerization step of depositing the hydrosilyl group-containing compound, the alkoxysilyl group-containing compound, and the catalyst on at least a part of the surface of the substrate, and polymerizing the hydrosilyl group-containing compound and the alkoxysilyl group-containing compound to form a silicon-containing polymer layer on the surface of the substrate; A surface-treated article, characterized in that it is produced by a surface treatment method comprising the steps of:
10. The substrate has a sheet-like shape, the silicon-containing polymer layer is a release layer; The surface treatment article is a release sheet. The surface-treated article according to claim 9 .
11. The surface-treated article according to claim 9 , wherein the silicon-containing polymer layer is a water-repellent layer.
Citation Information
Patent Citations
Film for molding fiber-reinforced plastics, and manufacturing method thereof
JP2012045795A
